The Imperative Power of Election Law on Money Politics - Muhammad Andi Septiadi; Alifa Salsabilla; Bima Bernadib; Luthfie Nugraha (Politeknik Negeri Bali, 2021)
Election rules have been regulated in Law no. 7 of 2017 where this rule contains imperative norms. The imperative norm talks about the rules that prohibit the practice of money politics during the electoral process. A rule is made to implement the function of controlling behavior in social and political life, when the rules are violated, the perpetrator will face legal proceedings and receive appropriate sanctions. Money politics and elections in Indonesia are commonplace for all people and are even considered to be cultured and inseparable. This research was made with the aim of reviewing imperative norms in the implementation of ineffective elections in preventing money politics practices. This study uses a qualitative research approach with triangulation technique analysis. From this study the authors found that the power of normative law in election activities in Indonesia is still relatively weak and a number of political practices continue to occur so that they can tarnish the democratic process